Theoretical and Experimental Studies on the Isomeric Vibrations of （3,4-difluoro） Phenylhydroquinone - 朱安峰 杨胜林 彭为亚 李光 江建明 (东华大学学报：英文版, 2011)
The （3,4-difluoro） Phenylhydroquinone （PHQ） have been successfully synthesized through the reaction of 3,4-difluoroaniline and 1,4-benzoquinone,and characterized by Fourier transform infrared spectroscopy（FTIR） and Raman spectroscopy.The ground-state geometries of the three PHQ isomers were distinguished using density functional theory（DFT） at the B3LYP/6-311G＋（d,p） level without symmetry constraints.The results show that the predicted FTIR and Raman spectra are highly consistent with experimental spectra.